Karakteristik Koefisien Absorpsi Bunyi dan Impedansi Panel Akustik dari Styrofoam Menggunakan Metode Tabung - Zahwa Khairunisa; Elvaswer Elvaswer (Jurnal Fisika Unand, 2024)
Research has been carried out regarding the sound absorption coefficient and impedance values of acoustic panels made from Styrofoam material, which aims to overcome sound noise. This research uses the impedance tube method, an acoustic material made from Styrofoam. Acoustic material samples are made from Styrofoam and have various shapes plain, non-perforated, perforated, serrated, ribbed, and hollow. The frequency ranges used in this research are 500 Hz, 1000 Hz, 2000 Hz, 4000 Hz, and 8000 Hz. The results of the study show that the highest sound absorption coefficient value is in the sample with a through hole with a hole diameter of 0.8 cm and a depth of 1.8 cm at a frequency of 1000 Hz, namely 0.99 and the lowest sound absorption coefficient value is at a frequency of 8000 Hz,0.78 in the sample Plain. The highest acoustic impedance value was obtained at a frequency of 1000 Hz, namely 4.16 dyne.s/cm5 with a sample with a through hole. This is influenced by the diameter of the hole and the depth on the surface of the Styrofoam. Styrofoam material can be used as a sound-absorbing material based on the sound absorption coefficient and acoustic panel impedance values.